MEASUREMENT OF SERVICE QUALITY AND CUSTOMER SATISFACTION (APPLICATION MODEL ON SERVICE COMPANY) - Mohammad Machrus (Prosiding International conference on Information Technology and Business (ICITB), 2015)
Success of a company in marketing service, isdetermined by service quality that must be satisfy thecustomers. Management should commit to maintainservice quality to keep customer satisfaction, becauseservice quality and customer service is dependanteach other. So it is necessary to measure themperiodically. Dimensions that have positivecorrelation with service quality and customersatisfaction are summarized in TERRA, i.e.:Tangible, Empathy, Reliability, Responsiveness, andAssurance. Beside that, there five gaps that causedservice quality cannot fulfill the customersatisfaction, those gaps are: 1) Gap betweenCustomer Expectation and Management Perception,2) Gap between Management Perception andServqual Specification, 3) Gap Between ServqualSpecification and Service Delivery, 4) Gap betweenService Delivery and External Communication, 5)Gap between Expected Service and PerceivedService. Service quality can be measured byPerformance and Important Ratio (PIP) model.Meanwhile, customer satisfaction can be measuredby model function : S = fs (E,P), where : S =Customer Satisfaction, E= Customer Expectation,and P = Perceived Performance.KEY WORDS: Servqual, Customer satisfaction,Tangible, Empaty, Reliability, Responsiveness,Assurance.